2015
DOI: 10.3109/0886022x.2015.1077324
|View full text |Cite
|
Sign up to set email alerts
|

Association of transforming growth factor-β1 polymorphisms with the risk of chronic kidney diseases

Abstract: The association of transforming growth factor-b1 (TGF-b1) polymorphisms with the risk of chronic kidney diseases (CKD) remains elusive. We aimed to perform a meta-analysis to evaluate the relationship between TGF-b1 polymorphisms and the susceptibility to CKD. Association studies were searched according to a defined criteria using electronic databases. The strength of association between TGF-b1 polymorphisms and CKD risk was evaluated by odds ratio (OR) with the corresponding 95% confidence interval (CI). Nine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…In our study, the TGF-β1 869 T > C variant genotype was present in 87.40% of mothers and in 79.90% of newborns. We also identified in our study that newborns with heterozygous or variant homozygous genotype (TC + CC) have a higher obesity risk, similar to the study of Mao, who showed that the CC genotype of the TGF-β1 869 T > C gene is associated with type 2 diabetes mellitus, thus representing a risk factor, [53] and also with Rodrigues’ study who pointed out that the CC genotype in patients with BMI under 25 kg/m 2 and TC genotype of the TGF-β1 869 T > C polymorphism in patients with BMI of 30 kg/m 2 are associated with type 2 diabetes mellitus. [54] …”
Section: Discussionsupporting
confidence: 88%
“…In our study, the TGF-β1 869 T > C variant genotype was present in 87.40% of mothers and in 79.90% of newborns. We also identified in our study that newborns with heterozygous or variant homozygous genotype (TC + CC) have a higher obesity risk, similar to the study of Mao, who showed that the CC genotype of the TGF-β1 869 T > C gene is associated with type 2 diabetes mellitus, thus representing a risk factor, [53] and also with Rodrigues’ study who pointed out that the CC genotype in patients with BMI under 25 kg/m 2 and TC genotype of the TGF-β1 869 T > C polymorphism in patients with BMI of 30 kg/m 2 are associated with type 2 diabetes mellitus. [54] …”
Section: Discussionsupporting
confidence: 88%
“…Khalil et al found that among patients with CKD of different origin, there was an association between SNP rs1800471 and rapid progression of CKD (Khalil et al, 2005). A previous meta-analysis by Mao et al evaluating the relation of TGF-b1 polymorphisms with CKD susceptibility reported similar findings for rs1800469 and rs1800470 (Mao et al, 2015). However, they did not find any association of rs1800471 with CKD, possibly because they calculated the pooled ORs using a relatively small sample size and applied distinct contrast models.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies have reported conflicting results relating to the association between TGF-β1 SNPs and CKD. An increased risk was noted with rs1800471 in a European population, 19 whereas a recent meta-analysis 33 has shown increased CKD risk (in the non-HIV-infected population) among Asians and a CKD-protective effect of another TGF-β1 variant. Therefore, the effect of TGF-β1 polymorphisms on CKD remains inconclusive.…”
Section: Discussionmentioning
confidence: 99%